2018
DOI: 10.1016/j.bioorg.2018.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel 1,2-bis-quinolinyl-1,4-naphthoquinones: ERK2 inhibition, cytotoxicity and molecular docking studies

Abstract: Two novel series of N-2,3-bis(6-substituted-4-hydroxy-2-oxo-1,2-dihydroquinolin-3-yl)naphthalene-1,4-diones 3a-d and substituted N-(methyl/ethyl)bisquinolinone triethyl-ammonium salts 4e,f were successfully synthesized. The synthesized compounds were targeted as new candidates to extracellular signal-regulated kinases 1/2 (ERK1/2) with considerable antineoplastic activity. The synthesis involved the reactions of 2 equivalents of 4-hydroxy-2(1H)-quinolinones 1a-f and one equivalent of 1,4-naphthoquinone (2) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Gene expression studies showed that p53, mouse double minute 2 homolog (Mdm-2) (a p53 regulator) and Bcl-2 (apoptosis inhibitor) were up-regulated during apoptosis induction by compound (61). 82) Two synthesized novel series of N-2,3-bis(6substituted-4-hydroxy-2-oxo-1,2-dihydroquinolin-3-yl)naphthalene-1,4-diones and substituted N-(methyl/ethyl)bisquinolinone triethylammonium salts were described as new candidates to extracellular signal-regulated kinases 1/2 (ERK1/2) with considerable antineoplastic activity. These compounds inhibited ETS-1 phosphorylation by ERK2 and showed highest potency for ERK2 inhibition with ATPcompetitive inhibition mechanism.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%
“…Gene expression studies showed that p53, mouse double minute 2 homolog (Mdm-2) (a p53 regulator) and Bcl-2 (apoptosis inhibitor) were up-regulated during apoptosis induction by compound (61). 82) Two synthesized novel series of N-2,3-bis(6substituted-4-hydroxy-2-oxo-1,2-dihydroquinolin-3-yl)naphthalene-1,4-diones and substituted N-(methyl/ethyl)bisquinolinone triethylammonium salts were described as new candidates to extracellular signal-regulated kinases 1/2 (ERK1/2) with considerable antineoplastic activity. These compounds inhibited ETS-1 phosphorylation by ERK2 and showed highest potency for ERK2 inhibition with ATPcompetitive inhibition mechanism.…”
Section: Cardioprotective and Anti-ischemic Propertiesmentioning
confidence: 99%
“…We also synthesized fused naphthofuro[3,2- c ]quinoline-6,7,12-triones VI , and pyrano[3,2- c ]quinoline-6,7,8,13-tetraones, VII that have shown potential as ERK inhibitors [19]. Whereas syntheses of bis(6-substituted-4-hydroxy-2-oxo-1,2-dihydro-quinolin-3-yl)-naphthalene-1,4-diones VIII and substituted N -(alkyl)bis-quinolinone triethyl-ammonium salts VIV , were explored as candidates for extracellular signal-regulated kinases 1/2 (ERK1/2) having antineoplastic activity [20].…”
Section: Instructionmentioning
confidence: 99%
“…Quinolones show a significant similarity to some anticancer [ 4 ], anticonvulsant [ 5 – 7 ], anti-dermatities [ 8 ], antibacterial [ 9 ], antimicrobial [ 10 ], anti-Alzheimer [ 11 ] and pain relief [ 12 ] in addition to their medical, agricultural and industrial uses [ 13 15 ]. In previous work with quinolones, Aly et al, synthesized various classes of 2-quinolones such as 2′-amino-2,5′-dioxo-5′,6′-dihydro-spiro(indoline-3,4′-pyrano[3,2- c ]quinoline)-3′-carbonitriles [ 16 ], 3-(methyl-thio)-4-oxo-4,5-dihydrofuro[3,2-c]quinolone-2-carbonitriles [ 17 ], 3-(methylthio)-4-oxo-4,5-dihydro-furo[3,2- c ]quinolone-2-carboxamides [ 17 ], naphtho[2′,3′:4,5]furo[3,2-c]quinoline-6,7,12(5 H )-trione derivatives (as ERK inhibitors with efficacy in BRAF-mutant Melanoma) [ 18 ], 2,3-bis-(4-hydroxy-2-oxo-1,2-dihydroquinolin-3-yl)succinates, arylmethylene-bis-3,3′-quinoline-2-ones [ 19 ], N -2,3-bis(6-substituted-4-hydroxy-2-oxo-1,2-dihydroquinolin-3-yl)naphthalene-1,4-diones and substituted N -(methyl/ethyl)bisquinolinone triethylammonium salts [ 20 ].…”
Section: Introductionmentioning
confidence: 99%